A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae), with a key to the species of the genus - Campos, Martha R.; Alexander, Moises (Zootaxa, 2020)
A new species of Phallangothelphusa Pretzmann, 1965, is described from the foothills of the Serranía de San Lucas, Antioquia Department, Colombia. The number of the species increases to six: P. dispar (Zimmer, 1912), P. magdalenensis Campos, 1998, P. juansei Campos, 2010, P. martensis Cardona & Campos, 2012, P. tangerina Campos, Lasso & Arias, 2019, and P. zenuorum n. sp. The new species is distinguished from its congeners mainly by the length of the exopod of the third maxilliped and by the morphology of the first and second male gonopods, particularly on the first male gonopod the outline of apex, the shapes of the mesial and lateral processes, and on the second one the shape of the distal endopod. An updated key for the identification of the species of Phallangothelphusa is given.